Ser mulher-mãe: a educação da saúde nas páginas da Eu Sei Tudo nas primeiras décadas do século XX (1918-1932) - Arminda Nela Martins Lopes Fernandes (2009)
In Brazil, as it happened in Europe, the turn of the 19th century to the 20th century can be characterized by the fascination of scientific discoveries. The science, considered the most elevated manifestation of the human intelligence, used to have the mission to tell the origin and the future of men and of the universe, as well as it used to have the responsibility to impose the rules for good behavior to all society. In the context of affirmation of urban place as a synthesisplace from the national modernity, there was an improvement of the written languages circulation, with the enlargement of the Brazilian publishing market and an increase of books, magazines and newspapers titles, such as: almanacs, magazines, campaigns pamphlets addressed to the childhood and to the feminine public. One of the printed matter that circulated in Brazil, in this period, was the magazine Eu Sei Tudo, published in Rio de Janeiro, from 1917 to 1958. This magazine, which was monthly published and circulated all over the country, has contributed not only with the dissemination of new habits and customs, but it also has participated on the formation of a social imaginary in the first decades of the 20th century. The medicine and the medical discourses about health were presented, in this magazine, as something wonderful, progressive, essential and beneficial to the society from that period. This research analyses the magazine Eu Sei Tudo in the period 1918 1932, focusing on the scientific divulgation about the hole of modern mothers on the care of their children. When we investigate how the magazine published certain knowledge and how it constituted new social holes, we have the intention to contribute to an understanding of the several dimensions of the pedagogical action and of the transformations of the familys action in the educational field.